ANALYSIS OF FREE AMINO ACID CONTENT IN ARVENSE AND RAMOSISSIMUM NEEDLES (Scientific journal of the Fergana State University, 2024)
The article describes methods of determining the amount of free amino acids in the above-ground part of two types of wild horsetail - Equisetum Arvense L. - field horsetail and Equisetum Ramosissimum D. - field horsetail. The results were presented in tabular form. Amino acids were studied using the Steven A. Cohen Daviel method using high-performance liquid chromatography (HPLC).